One-Step synthesis of highly luminescent carbon dots in noncoordinating solvents - Wang, F.; Pang, S.; Wang, L.; Li, Qin; Kreiter, M.; Liu, C. (American Chemical Society, 2010)
A novel one-step approach for synthesizing highly luminescent oil soluble carbon dots (quantum yield: 53%) and water-soluble carbon dots is introduced. The superior luminescence efficiency, together with the simple, rapid, and reproducible synthesis method will facilitate fundamental studies and promising practical applications of these carbon-based quantum dots.